2020
DOI: 10.2298/hemind190925008n
|View full text |Cite
|
Sign up to set email alerts
|

Liquid transfer properties of textile fabrics as a function of moisture content

Abstract: Liquid transport in textile fabrics determines thermal comfort during high physical activity of a person when liquid perspiration is produced and needs to be transferred away from the skin to keep the thermal balance. In this investigation, an attempt was made to get some indications of how the combination of the fabric composition, geometry and dimensional stability, and the moisture content influences liquid transfer properties of plain weft knitted fabrics. Therefore, the knitted fabrics made from pure hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Specifically, K3 and K6 have shown the lowest reduction in liquid accumulation at elevated temperatures which can be ascribed to their higher volume-specific area arising from the profiled fibers that is Coolmax in K3 and micro denier polyester in K6. 49,63…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, K3 and K6 have shown the lowest reduction in liquid accumulation at elevated temperatures which can be ascribed to their higher volume-specific area arising from the profiled fibers that is Coolmax in K3 and micro denier polyester in K6. 49,63…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, K3 and K6 have shown the lowest reduction in liquid accumulation at elevated temperatures which can be ascribed to their higher volume-specific area arising from the profiled fibers that is Coolmax in K3 and micro denier polyester in K6. 49,63 The amount of liquid discharged during P1, according to Figure 13(d), was reduced by almost half in most of the fabrics for temperature controlled NSS, and a strong positive correlation (R 2 ¼ 0.74) was observed between the amount of liquid discharged during P1 at temperature controlled and non-temperature controlled NSS. Particularly, the lowest liquid discharge was observed in K3 and K6 at temperature controlled NSS, accounting for 0.15 and 0.28 times their values at non-temperature controlled NSS, respectively.…”
Section: Correlation Between Nss Flow Rates and Liquid Mass Distributionmentioning
confidence: 90%
“…The first one affects the air exchange between the textile microclimate and ambient air and provides heat and mass transfer, 5 while the second gives information about the fiber accessibility to water vapor 6 and influences the fabric’s thermal insulation. 7 Another piece of the fabric quality puzzle belongs to pilling propensity. Researchers identified that the synergism of fiber, yarn, and fabric properties determines the fabric pilling propensity.…”
Section: Introductionmentioning
confidence: 99%